Die Morphonemklassifikation der modernen englischen Sprache - Dovgun, Irina (My University, 2015)
The definition of the morphoneme as an abstract unit of morphonology which is used for the description of the morphologically conditioned phonemic changes in the morphs of a morpheme is given and the classification of the morphonemes of the word change paradigm in Modern English is presented in the article. The morphonemes are grouped according to the parts of speech; the differential features of the phonemes; the number of the morphs of a certain morpheme; the number of the phonemes in a morpheme; the number of the grammatical meanings. The functions of the morphonemes in the language are studied.
Keywords: морфонема; фонемні чергування; фонемные чередования; morphoneme; phonemic changes; кафедра іноземних мов професійного спрямування